Noblestitch® system for PFO closure: A novel but judicious alternative to traditional devices—A case report - Onorato, Eustaquio Maria; Grancini, Luca; Monizzi, Giovanni; Mastrangelo, Angelo; Fabbiocchi, Franco; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2023)
Background: Percutaneous suture-mediated patent foramen ovale (PFO) closure has recently been used with the aim to avoid a double-disc nitinol device implantation. This novel technique has been carried out successfully in several centers offering PFO closure with an effective closure rate comparable to conventional double-disc devices. Case Summary: A 50-year-old man, pentathlon athlete, suffering from previous left sided ischemic stroke underwent percutaneous closure of a permanent right-to-left shunt (RLS) via PFO with large fenestrated septum primum aneurysm (ASA) at another institution. The NobleStitch® system was successfully implanted using local anesthesia and under angiographic-fluoroscopic monitoring. He was discharged home on aspririn 100 mg daily with moderate residual shunt at contrast transthoracic echocardiography (cTTE) that persisted unaltered at subsequent controls. Seven months later, unable to resume sporting activity because of physical discomfort and dyspnea on exertion, the patient asked for a second opinion at our Heart & Brain clinic. Two-dimensional (2D) TTE showed septum primum laceration next to radiopaque polypropylene knot with a moderate bidirectional shunt located at the fenestrated septum primum far from the PFO site. A catheter-based closure of the septal defect was therefore planned under local anesthesia and rotational intracardiac echo monitoring. An equally sized discs 28.5x28.5 mm Flex II UNI occluder (Occlutech GmbH, Jena, Germany) was successfully implanted across the atrial septal defect without complications. The patient was discharged in good clinical conditions; dual antiplatelet therapy (aspirin 100 mg/daily and clopidogrel 75 mg/daily) was recommended for two months and then single antiplatelet therapy (aspirin100 mg/daily) up to six months. Abolition of the residual shunt was confirmed at 1- and 6-month follow-up by contrast Transcranial Doppler (cTCD) and 2D color Doppler cTTE. Discussion: Closing a PFO with a suture-base system, without leaving a device implant behind, may be a cutting-edge technology and potential alternative to traditional devices. Nevertheless, meticulous selection of the PFO anatomies by 2D TEE is key for a successful closure procedure in order to avoid complications that must be managed again with a second percutaneous procedure or by surgery.